If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x(6x + -6) = 0 Reorder the terms: 2x(-6 + 6x) = 0 (-6 * 2x + 6x * 2x) = 0 (-12x + 12x2) = 0 Solving -12x + 12x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '12x'. 12x(-1 + x) = 0 Ignore the factor 12.Subproblem 1
Set the factor 'x' equal to zero and attempt to solve: Simplifying x = 0 Solving x = 0 Move all terms containing x to the left, all other terms to the right. Simplifying x = 0Subproblem 2
Set the factor '(-1 + x)' equal to zero and attempt to solve: Simplifying -1 + x = 0 Solving -1 + x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + x = 0 + 1 x = 0 + 1 Combine like terms: 0 + 1 = 1 x = 1 Simplifying x = 1Solution
x = {0, 1}
| 8d-6(2d-4)=8 | | 4n+5(7n-3)=9(9-5) | | -6(6-5p)-8p=118 | | 3(20+13)= | | 7x=-6-9z | | -3x+11=10 | | 3(3m+1)-4=17 | | 7(-3)-2/(6(-3)) | | 3(20+5)= | | 6x+10+x=45 | | 12+n/4=o | | 1/3x+7=27 | | 18+16m=63+3m | | x^2-3x-14=4 | | -4(1+4n)-7n=111 | | 4x-(-7)=-17 | | 2m-5=14 | | 21m+5=15m+7 | | 20=4x^2-16x-20 | | y=64x+10 | | m+33=54 | | x^2+2x+2=65 | | 2x-3+4=-13 | | 5a(a-3)= | | 2x-3+4=13 | | y+3x=27 | | 2x+20=2x^2 | | 17+6w=23 | | x/5-5=-13 | | 18+6w=23 | | 14x^3+21x^2+16x+24=0 | | -0.75x+0.5=6.5 |